2008
DOI: 10.1021/bc800262m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Molecular Charge on the Biodistribution of Bombesin Analogues Labeled with the [99mTc(CO)3]-Core

Abstract: The overexpression of Bombesin (BBS) receptors on a variety of human cancers make them interesting targets for tumor imaging and therapy. Analogues of the neuropeptide BBS have been functionalized with the (NalphaHis)- chelator for labeling with the 99mTc-tricarbonyl core. The introduction of a betaAla-betaAla linker between the stabilized BBS binding sequence and the chelator led to increased tumor uptake but still rather unfavorable in ViVo properties. Novel polar linkers, with different charge, have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 33 publications
0
77
0
Order By: Relevance
“…Stability of such linker to peptidases should be taken into account, as it has been shown by García Garayoa and coworkers [123][124][125] in a series of studies on bombesin analogues labelled with 99m Tc(CO) 3 using retro[Ncarboxymethyl-histidine]. Blood plasma stability of radiopeptides with three linkers: 3,6-dioxa-8-aminooctanoic acid, Ala-Ala and Lys(sha)-Ala-Ala (sha = shikimic acid) and a conjugate without linker were compared.…”
Section: Stability Of Peptide To Blood-borne Peptidasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stability of such linker to peptidases should be taken into account, as it has been shown by García Garayoa and coworkers [123][124][125] in a series of studies on bombesin analogues labelled with 99m Tc(CO) 3 using retro[Ncarboxymethyl-histidine]. Blood plasma stability of radiopeptides with three linkers: 3,6-dioxa-8-aminooctanoic acid, Ala-Ala and Lys(sha)-Ala-Ala (sha = shikimic acid) and a conjugate without linker were compared.…”
Section: Stability Of Peptide To Blood-borne Peptidasesmentioning
confidence: 99%
“…The chemical nature of the linker may also influence its effect on the affinity. Three linkers containing 3 hGlu and Ala ( 3 hGluAla-Ala, 3 hGlu-3 hGlu-Ala, and 3 hGlu-3 hGlu-3 hGlu) were investigated in order to increase the hydrophilicity of 99m Tc(CO) 3 -retro[N -carboxymethyl-histidine]-BBN (7)(8)(9)(10)(11)(12)(13)(14) conjugates [125]. It was found that the introduction of two charged amino acids increased the hydrophilicity while keeping the affinity, but the affinity was decreased by a linker containing only charged amino acids.…”
Section: Affinity Of Radiolabelled Conjugate To Its Molecular Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…Tc-labeled derivatives of bombesin (BBS), [22,33] a regulatory peptide that targets the gastrin-releasing peptide (GRP) receptor, which is overexpressed in various tumor types such as prostate, breast, and small-cell lung cancer. [34] Like other radiolabeled regulatory peptides potentially useful as imaging probes for the detection of tumors and metastasis, [35] radiotracers derived from BBS or its binding sequence BBS (7)(8)(9)(10)(11)(12)(13)(14) are rapidly degraded both extracellularly and intracellularly by peptidases.…”
Section: In Vitro and In Vivo Evaluationmentioning
confidence: 99%
“…[12,33] Alkyne 17 equipped with the albumin binding molecule C (Scheme 3) was conjugated to azidopeptide 23 by CuAAC in a mixture of water and ethanol at 60 8C to yield BBS(7-14) derivative L24. Reference compound N a HisAc-BBS (7)(8)(9)(10)(11)(12)(13)(14), identical in all respects but lacking the albumin binding moiety and functionalized with the established N(a)-HisAc chelating system, was prepared by SPPS.…”
Section: In Vitro and In Vivo Evaluationmentioning
confidence: 99%